2020
DOI: 10.3952/physics.v60i4.4359
|View full text |Cite
|
Sign up to set email alerts
|

Long-time drift induced changes in electrical characteristics of graphene–metal contacts

Abstract: Chemical vapour deposition (CVD) graphene is commonly recognized as promising 2D material for development of electronic devices. However, the long-term drift of electrical parameters still requires deeper understanding before the technological means can be selected for an individual type of the devices. In this work, the changes in the electrical resistance were investigated over long time in the planar samples based on the CVD graphene with Au and Ni contacts. The samples were arranged as arrays of the resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…As shown in Figure 2a, there is a notable difference in the phase lag between the bare Au surface and the graphene-supported Au film, amounting to approximately 10 degrees. Previous RAMAN spectroscopy studies confirmed that the areas represented by darker regions in the scanned phase image (Figure 2a) indicate the presence of the graphene layer [17]. The cross-section (Figure 2c) along the red solid line in Figure 2b reveals that the distance between the nearest peaks or valleys exceeds the radius of the SPM tip used in our experiments, typically falling within the range of 5-55 nm.…”
Section: Methodssupporting
confidence: 76%
See 1 more Smart Citation
“…As shown in Figure 2a, there is a notable difference in the phase lag between the bare Au surface and the graphene-supported Au film, amounting to approximately 10 degrees. Previous RAMAN spectroscopy studies confirmed that the areas represented by darker regions in the scanned phase image (Figure 2a) indicate the presence of the graphene layer [17]. The cross-section (Figure 2c) along the red solid line in Figure 2b reveals that the distance between the nearest peaks or valleys exceeds the radius of the SPM tip used in our experiments, typically falling within the range of 5-55 nm.…”
Section: Methodssupporting
confidence: 76%
“…A thin Au layer was formed on the Si plate using DC magnetron sputtering. Commercial chemical vapor deposition (CVD)-grown graphene monolayer (Graphenea) was then transferred via standardized wet transfer method on the Au film [17]. Pt probe (Pt-rock, model RMN12Pt400B, Bruker, Billerica, MA, USA) was placed on top of the structure and used as an electrode for measurements.…”
Section: Methodsmentioning
confidence: 99%
“…The most common technique used for creating graphene is chemical vapour deposition (CVD) which can create grain boundaries and regions with varying thickness [7], leading to a difference in resistance and performance between sensors. There is also the issue of doping from environmental sources, mainly water, causing a drift in graphene resistance over time [8].…”
Section: Motivationmentioning
confidence: 99%